Impact Of Money Market Reforms On Economic Growth Of Nigeria 1990 – 2017 - Uruakpa, Peter C. (Archives of Business Research, 2019)
This study examined the impact of money market reforms on economic growth of Nigeria. The objectives were to find out how reform of the market since 1990 has impacted on Nigeria’s GDP through money market transactions, treasury bill rate and treasury bill outstanding. Quasi experimental design was adopted. Data were collected through CBN Statistical Bulletin covering the period 1990-2017. Statistical tools adopted include unit root test, OLS, cointegration and variance decomposition. Findings showed that the variables are non-stationary but integrated in order 1 level. The cointegration result showed that all the variables are co-integrated. The OLS result suggests that money market value has positive and significant effect on GDP while treasury bill outstanding has positive but insignificant effect on GDP. However, treasury bill rate has negative and significant effect on GDP. The F-statistics suggests that all the money market proxies jointly impacted of GDP, an implication that money market is a viable financial market in Nigeria. Moreover, the variance decomposition showed that GDP has a decreasing variance with money market value and treasury bill rate but an increasing variance with treasury bill outstanding. The variance impulse showed that GDP responds to the activities or movement in money market value and treasury bill rate. In conclusion, it was observed that money market reform has helped boost the effect of the market on Nigeria’s economic growth. The study recommends constant reform of the market. It urges the authorities of the market to deepen the market with more trading instruments.